Field comparison of portable and stationary instruments for outdoor urban air exposure assessments. (December 2015) - Viana, M.; Rivas, I.; Reche, C.; Fonseca, A.S.; Pérez, N.; Querol, X.; Alastuey, A.; Álvarez-Pedrerol, M.; Sunyer, J.
Abstract: The performance of three portable monitors (micro-aethalometer AE51, DiscMini, Dusttrak DRX) was assessed for outdoor air exposure assessment in a representative Southern European urban environment. The parameters evaluated were black carbon, particle number concentration, alveolar lung-deposited surface area, mean particle diameter, PM10, PM2.5 and PM1 . The performance was tested by comparison with widely used stationary instruments (MAAP, CPC, SMPS, NSAM, GRIMM aerosol spectrometer). Results evidenced a good agreement between most portable and stationary instruments, with R 2 values mostly >0.80. Relative differences between portable and stationary instruments were mostly <20%, and <10% between different units of the same instrument. The only exception was found for the Dusttrak DRX measurements, for which occasional concentration jumps in the time series were detected. Our results validate the performance of the black carbon, particle number concentration, particle surface area and mean particle diameter monitors as indicative instruments (tier 2) for outdoor air exposure assessment studies. Graphical abstract: Highlights: Epidemiological studies highlight the need for exposure assessment studies. Portable and stationary monitors were compared for exposure assessment. Good agreements were found: R 2 mostly >0.80; relative differences <20%. Relative differences were <10% between different units of the same instrument. Parameters assessed were BC, N, LDSA and mean particle diameter, in outdoor air. Abstract : Portable monitors evaluated for BC, and particle number, mean size, and surface area are suitable instruments for population exposure assessments in urban outdoor air.